Data Protection and Interoperability in EU External Relations : Guaranteeing Global Data Transfers in the Area of Freedom, Security and Justice - Tassinari, Francesca (International Law E-Books Online, Collection 2025., 2024)
This book assesses whether the implementation of transborder interoperable solutions aligns with the European Union's standards and rules on personal data transfer. It specifically examines the principles and values enshrined in the founding Tre